ENHANCING CONCEPTUAL THINKING ABILITY OF EARLY CHILDHOOD USING LOOSE PARTS PLAY ACTIVITIES - Charoensrithongkun, Pailin; Rattanakiat, Peeraporn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objective of this research was to compare the conceptual thinking of early childhood students before and after providing the loose parts play activities. The sample consisted of 16 male and female students aged 4–5 years studying in Kindergarten Year 2 in the 1st semester of 2022 Academic year, Ban Dongkeng School under Khon kaen Primary Educational Service Area Office 3. The research Instruments were 1) plans for loose parts play activities, 2) a conceptual thinking test of early childhood. The data were statistically analyzed by mean, standard deviation, and relative development score. The finding of this research was the conceptual thinking of childhood students after learning using loose parts play activity was higher than before.The research finding was the conceptual thinking of early childhood students was higher with 34.19 average scores, 2.71 standard deviation, and 84.00 relative development of all aspects scores after providing the loose parts play activities.